Integrating Technology and Enhancing Communication: Pre-Service Teachers’ Perceptions and Collaborative Podcast Creation in English Language Education - Weni Pratiwi; Rita Inderawati; Sary Silvhiany (STAI Hubbulwathan Duri, 2024)
The integration of technology into education has transformed traditional teaching methods, with podcasting emerging as a promising technique to enhance language acquisition. This study examines how collaborative podcasting influences pre-service teachers’ communication skills and their perceptions of technology’s role in English language education. Using a survey method, data were collected from fourth, sixth, and eighth-semester students who had created podcasts. Google Forms facilitated the distribution of surveys via WhatsApp groups, ensuring broad participation. Quantitative data were gathered through Likert scale items, while qualitative feedback provided deeper insights. Descriptive analysis was used to calculate mean and standard deviation for each item. The findings revealed that collaborative podcasting enhanced students’ communication skills, including clarity, active listening, and teamwork. Students reported personalized learning experiences and active engagement in content creation, which fostered a supportive and interactive learning environment. The results also highlighted positive perceptions of technology as a valuable tool for language learning. Collaborative podcasting not only improved communication skills but also demonstrated the potential of technology to transform learning by promoting active participation and critical skills development. These outcomes underscore the value of podcasting in preparing pre-service teachers for real-world communication challenges. Technology integration through collaborative podcast projects positively impacts pre-service teachers' communication skills and engagement. Educators are encouraged to incorporate podcasting into language curricula to enhance skill development. Future research should explore long-term effects of podcasting on language acquisition and the adaptability of technological tools for diverse learning styles.